Peculiarities of formation of secondary sexual characteristics and menstrual function in girls with hyperandrogenism during puberty - A. A. Talibli (Акушерство, гинекология и репродукция, 2020)
Aim: to study the peculiarities of the formation of secondary sexual characteristics and menstrual function in girls with hyperandrogenism (HA) during puberty.Materials and methods. We examined 137 adolescent girls with HA aged 12–17 years. All examined girls were divided into 3 groups: 12–13 years (Group I, n = 27); 14–15 years (Group II, n = 63); 16–17 years (Group III, n = 47). The intensity of secondary sexual characteristics was determined by Tanner scale; the severity of hirsutism was assessed by Ferriman–Galway scale. The studied parameters were compared with previously published data from 42 girls without HA symptoms with normal indicators of physical and sexual development that were also divided into 3 age groups: 12–13 years (n = 16), 14–15 years (n = 14), 16–17 years (n = 12).Results. Girls with HA in puberty, starting from 14–15 years, had marked reduction of mammary glands and enhancement of axillary and suprapubic hair growth. In 32.8 % of girls with HA menstrual function was normal; in 67.1 % menses disorders and menstrual irregularities were observed that manifested by opsomenorrhea (31.5 %), juvenile bleedings (19.6 %), oligomenorrhea (18.5 %), amenorrhea (16.3 %), algodismenorrhea (14.1 %).Conclusion. HA in puberty, regardless of origin that caused this pathology, is a high risk factor for pathologies of sexual development and the formation of menstrual dysfunction.